How can interventions increase motivation for physical activity? A systematic review and meta-analysis. Issue 3 (3rd July 2018) - Knittle, Keegan; Nurmi, Johanna; Crutzen, Rik; Hankonen, Nelli; Beattie, Marguerite; Dombrowski, Stephan U
ABSTRACT: Motivation is a proximal determinant of behaviour, and increasing motivation is central to most health behaviour change interventions. This systematic review and meta-analysis sought to identify features of physical activity interventions associated with favourable changes in three prominent motivational constructs: intention, stage of change and autonomous motivation. A systematic literature search identified 89 intervention studies ( k = 200; N = 19, 212) which assessed changes in these motivational constructs for physical activity. Intervention descriptions were coded for potential moderators, including behaviour change techniques (BCTs), modes of delivery and theory use. Random effects comparative subgroup analyses identified 18 BCTs and 10 modes of delivery independently associated with changes in at least one motivational outcome (effect sizes ranged from d = 0.12 to d = 0.74). Interventions delivered face-to-face or in gym settings, or which included the BCTs 'behavioural goal setting', 'self-monitoring (behaviour)' or 'behavioural practice/rehearsal', or which combined self-monitoring (behaviour) with any other BCT derived from control theory, were all associated with beneficial changes in multiple motivational constructs (effect sizes ranged from d = 0.12 to d = 0.46). Meta-regression analyses indicated that increases in intention and stage of change, but not autonomous motivation, were significantly related to increases in physical activity. The intervention characteristics associated with changes in motivation seemed to form clusters related to behavioural experience and self-regulation, which have previously been linked to changes in physical activity behaviour. These BCTs and modes of delivery merit further systematic study, and can be used as a foundation for improving interventions targeting increases in motivation for physical activity.